The feasibility of a self-management programme (My Life After Stroke; MLAS) for stroke survivors. Issue 2 (16th January 2023) - Johnson, V. L.; Apps, L.; Kreit, E.; Mullis, R.; Mant, J.; Davies, M. J.; ,
Abstract: Purpose: An evidence-based, theory-driven self-management programme "My Life After Stroke" (MLAS) was developed to address the longer-term unmet needs of stroke survivors. This study's aim was to test the acceptability and feasibility of MLAS as well as exploring what outcomes measures to include as part of further testing. Methods: Stroke registers in four GP practices across Leicester and Cambridge were screened, invite letters sent to eligible stroke survivors and written, informed consent gained. Questionnaires including Southampton Stroke Self-Management Questionnaire (SSSMQ) were completed before and after MLAS. Participants (and carers) attended MLAS (consisting of two individual appointments and four group sessions) over nine weeks, delivered by two trained facilitators. Feedback was gained from participants (after the final group session and final individual appointment) and facilitators. Results: Seventeen of 36 interested stroke survivors participated alongside seven associated carers. 15/17 completed the programme and attendance ranged from 13–17 per session. A positive change of 3.5 of the SSSMQ was observed. Positive feedback was gained from facilitators and 14/15 participants recommended MLAS (one did not respond). Conclusions: MLAS was a feasible self-management programme for stroke survivors and warrants further testing as part of the Improving Primary Care After Stroke (IPCAS) cluster randomised controlled trial. IMPLICATIONS FOR REHABILITATION: My Life After Stroke is a self-management programme developed for stroke survivors living in the community. MLAS is feasible and acceptable to stroke survivors. MLAS could be considered to help address the unmet educational and psychological needs of stroke survivors.